Characterization of homicide and associated factors with use of drugs in a state capital city in Northeast Brazil - Veloso, Alline Oliveira do Nascimento; Keomma, Kaio; Coutinho, Mayrla Sousa; Cavalcanti, Alessandro Leite (ABCS Health Sciences, 2019)
Introduction: Homicide is a public health problem in Brazil that is often related to illicit drugs. Objective: To characterize homicides and aspects associated with the use of illicit drugs. Methods: A cross-sectional study with a quantitative approach carried out in Joao Pessoa, in the state of Paraiba, Brazil, in 2014. 424 homicide victims whose data were collected through a specific instrument were considered, analyzed descriptively and analytically with the aid of statistical software, with Chi Squared Test and Robust Poisson Regression, considering a confidence level of 95% and statistical significance when p<0.05. Results: Prevalence of homicide victims (93.2%), non-whites (97.2%), with up to 30 years, considering the age groups below 20 years (22.6%), 20-24 (26.7%) and 25 to 29 (18.8%), with less than seven years of study (67.5%), with a history of involvement with illicit drugs (72.5%) and incarceration (59,7%). There was an association between involvement with illicit drugs with sex (p=0.037), age (p=0.002) and history of incarceration (p<0.001). There was a 67% higher prevalence of involvement with illicit drugs among those with a history of incarceration (PR: 1.67, 95% CI: 1.44-1.94) and 28% lower among individuals aged 30 years or older (PR: 0.72, CI: 0.58-0.88). Conclusion: Homicide is part of a complex set of social issues, including involvement with illicit drugs, which is more prevalent among young adults and individuals with a history of incarceration.